The impact of COVID-19 on agrifood systems and rural areas in Central Asia and Caucasus countries: Final report of a study commissioned by FAO - Nodir Djanibekov; Thomas Herzfeld (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
This report contributes to the project "Securing agriculture and rural development in times of COVID-19, pathways to regional responses for recovery, reforms, and resilience" by the Food and Agriculture Organization of the United Nations (FAO). The objectives of the report are threefold: 1) to assess the multiple impacts of the COVID-19 pandemic on agriculture, food security, and rural community; 2) to review the policy responses taken by the governments of eight Central Asia and Caucasus (CAC) countries to mitigate the effects of the crisis, and 3) to provide contextual options to build the resilience of the agricultural sector during post-COVID-19 recovery and against future shocks.
urn:nbn:de:101:1-2022021409452364906733
Keywords: 330; Coronavirus; Wirkungsanalyse; Landwirtschaft; Agrarproduktion; Lieferkette; Ernährungssicherung; Landbevölkerung; Zentralasien; Kaukasus